Mottled Mice and Non-Mammalian Models of Menkes Disease - Lenartowicz, Małgorzata; Krzeptowski, Wojciech; Lipiński, Paweł; Grzmil, Paweł; Starzyński, Rafał; Pierzchała, Olga; Møller, Lisbeth Birk (Frontiers in Molecular Neuroscience, 2015)
Menkes disease is a multi-systemic copper metabolism disorder caused by mutations in the X-linked ATP7A gene and characterised by progressive neurodegeneration and severe connective tissue defects. The ATP7A protein is a Copper (Cu)-transporting ATPase expressed in all tissues and plays a critical role in the maintenance of copper homeostasis in cells of the whole body. ATP7A participates in copper absorption in the small intestine and in copper transport to the CNS across the blood-brain-barrier and blood–cerebrospinal fluid- barrier. Cu is essential for synaptogenesis and axonal development. In cells, ATP7A participates in the incorporation of copper into Cu-dependent enzymes during the course of its maturation in the secretory pathway. There is a high degree of homology (>80% ) between the human ATP7A and murine Atp7a genes. Mice with mutations in the Atp7a gene, called mottled mutants, are well-established and excellent models of Menkes disease. Mottled mutants closely recapitulate the Menkes phenotype and are invaluable for studying Cu-metabolism. They provide useful models for exploring and testing new forms of therapy in Menkes disease. Recently, non-mammalian models of Menkes disease, Drosophila melanogaster and Danio rerio mutants were used in experiments which would be technically difficult to carry out in mammals.